Penerapan Metode Waterfall Pada Aplikasi Simpan Pinjam Credit Union Kayuh Nusantara Berdikari - Riski - Annisa; Yulia Yulia; Murdiansyah Murdiansyah (Teknik Informatika Universitas Pamulang, 2022)
Credit Union (CU) Kayuh Nusantara Berdikari is a community service cooperative in savings and loans. Based on the analysis that has been done, the Credit Union (CU) of Kayuh Nusantara Berdikari is still recapitulating one by one cash inflow and outflow transactions which are sourced from notes and then copied to Ms. Excel to be used as financial reports. Data processing like this requires a long time and effort, errors in data processing have an impact on the quality of information in financial reports. Therefore, to create a savings and loan application for the Paddle Nusantara Berdikari Credit Union (CU) that uses the waterfall model as a software development method consisting of software requirements analysis, design, program code generation and testing. Data collection techniques used consisted of observation, interviews and literature study. The system built provides facilities such as processing employee data, account data, customer data, lending, savings, installments and fees as well as accessing financial reports. The savings and loan application that was built is expected to help improve the performance of saving and loan data processing at the Credit Union (CU) of Kayuh Nusantara Berdikari.